Cognitive Biases in the Era of COVID-19 : A Case of Clostridium sporogenes Bacteremia in a Patient with Small Bowel Obstruction - Marc J. Vecchio; Matthew Jankowich; Hassan Qadir; Melissa Gaitanis; Anupama Menon (Case Reports in Infectious Diseases)
Clostridium sporogenes bacteremia in immunocompetent patients is rare with very few reported cases in the literature. We present a case of Clostridium sporogenes bacteremia in an 81-year-old immunocompetent man with small bowel obstruction and hypoxemia during the COVID-19 pandemic. Routine monitoring of prognostic inflammatory markers for COVID-19 created a unique challenge in the management of our patient who developed sepsis with respiratory symptoms. Upon review, bacteremia from Clostridium sporogenes was associated with high mortality rates and could produce similar elevations in the inflammatory markers observed in COVID-19 pneumonia. Further, we reviewed the cognitive biases encountered when monitoring these inflammatory markers during the management of our patient with Clostridium sporogenes bacteremia, who was initially thought to have COVID-19 disease. While our patient ultimately tested negative for COVID-19, early administration of empiric antimicrobial therapy without source control failed to prevent clinical decompensation.